To factor this collect the like terms..2y would go with -7y to make -5y etc. Then factor the expression by factoring out 9 Your final answer should be 9(1-y+x^2)
If you need to simplify this calculate the sum or difference between numbers (3-1+7=9)
Your final answer for this should be 9-9y+9x^2
Hope this helps!
Hope this image helps!!!!!
The significant components, the radius and the height, are in inches and feet respectively, you'd need to convert them both to the same unit, whichever it may be, meters or feet or inches or millimeters, so long is the same, then use the volume of a cylinder equation to get it.
Answer:
(a) 7.6%
(b) 46.2% 42.4%
Step-by-step explanation:
(a)According to the definition of Continuous probability distribution
![f(x) = \frac{d}{dx}F(x)](https://tex.z-dn.net/?f=f%28x%29%20%3D%20%5Cfrac%7Bd%7D%7Bdx%7DF%28x%29)
![f(x) = \frac{F(x + h) - F(x - h)}{(x + h) - (x - h)}](https://tex.z-dn.net/?f=f%28x%29%20%3D%20%5Cfrac%7BF%28x%20%2B%20h%29%20-%20F%28x%20-%20h%29%7D%7B%28x%20%2B%20h%29%20-%20%28x%20-%20h%29%7D)
![f(69) = \frac{F(69 + 0.2) - F(69 - 0.2)}{0.4}](https://tex.z-dn.net/?f=f%2869%29%20%3D%20%5Cfrac%7BF%2869%20%2B%200.2%29%20-%20F%2869%20-%200.2%29%7D%7B0.4%7D)
⇒ 0.19 × 0.4 = F(69.2) - F(68.8)
⇒ F(69.2) - F(68.8) = 0.076
⇒ 7.6%
(b) Given F(69) = 0.5
![f(x) = \frac{d}{dx}F(x)](https://tex.z-dn.net/?f=f%28x%29%20%3D%20%5Cfrac%7Bd%7D%7Bdx%7DF%28x%29)
![f(x) = \frac{F(x) - F(x - h)}{x - (x - h)}](https://tex.z-dn.net/?f=f%28x%29%20%3D%20%5Cfrac%7BF%28x%29%20-%20F%28x%20-%20h%29%7D%7Bx%20-%20%28x%20-%20h%29%7D)
![f(69) = \frac{F(69) - F(69 - 0.2)}{0.2}](https://tex.z-dn.net/?f=f%2869%29%20%3D%20%5Cfrac%7BF%2869%29%20-%20F%2869%20-%200.2%29%7D%7B0.2%7D)
⇒ 0.19 × 0.2 = F(69) - F(68.8)
⇒ F(68.8) = 0.5 - 0.038 = 0.462
⇒ 46.2%
![f(x) = \frac{d}{dx}F(x)](https://tex.z-dn.net/?f=f%28x%29%20%3D%20%5Cfrac%7Bd%7D%7Bdx%7DF%28x%29)
![f(x) = \frac{F(x) - F(x - h)}{x - (x - h)}](https://tex.z-dn.net/?f=f%28x%29%20%3D%20%5Cfrac%7BF%28x%29%20-%20F%28x%20-%20h%29%7D%7Bx%20-%20%28x%20-%20h%29%7D)
![f(69) = \frac{F(69) - F(69 - 0.4)}{0.4}](https://tex.z-dn.net/?f=f%2869%29%20%3D%20%5Cfrac%7BF%2869%29%20-%20F%2869%20-%200.4%29%7D%7B0.4%7D)
⇒ 0.19 × 0.4 = F(69) - F(68.8)
⇒ F(68.8) = 0.5 - 0.076 = 0.424
⇒ 42.4%
Answer:
here you go
Step-by-step explanation:
W = (0.6) L
P = 2 ( L + W )
P = 2 [ L + (0.6) L ]
P = 2 ( 1.6 L )
P = (3.2) L
P = (3.2) x